Neural circuitry for maternal oxytocin release induced by infant cries - Valtcheva, Silvana; Issa, Habon A.; Bair-Marshall, Chloe J.; Martin, Kathleen A.; Jung, Kanghoon; Zhang, Yiyao; Kwon, Hyung-Bae; Froemke, Robert C. (Nature (London), 2023)
Oxytocin is a neuropeptide that is important for maternal physiology and childcare, including parturition and milk ejection during nursing 1 – 6 . Suckling triggers the release of oxytocin, but other sensory cues—specifically, infant cries—can increase the levels of oxytocin in new human mothers 7 , which indicates that cries can activate hypothalamic oxytocin neurons. Here we describe a neural circuit that routes auditory information about infant vocalizations to mouse oxytocin neurons. We performed in vivo electrophysiological recordings and photometry from identified oxytocin neurons in awake maternal mice that were presented with pup calls. We found that oxytocin neurons responded to pup vocalizations, but not to pure tones, through input from the posterior intralaminar thalamus, and that repetitive thalamic stimulation induced lasting disinhibition of oxytocin neurons. This circuit gates central oxytocin release and maternal behaviour in response to calls, providing a mechanism for the integration of sensory cues from the offspring in maternal endocrine networks to ensure modulation of brain state for efficient parenting. Experiments in mice identify a neural circuit that relays information about infant cries from the maternal auditory thalamus to hypothalamic oxytocin neurons to induce the release of oxytocin and modulate maternal behaviour.